2023
DOI: 10.1101/2023.04.24.538096
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selective Vulnerability of Layer 5a Corticostriatal Neurons in Huntington’s Disease

Abstract: The properties of the cell types that are most vulnerable in the Huntington's disease (HD) cortex, the nature of somatic CAG expansion of mHTT in these cells, and their importance in CNS circuitry have not been delineated. Here we have employed serial fluorescence activated nuclear sorting (sFANS), deep molecular profiling, and single nucleus RNA sequencing (snRNAseq) to demonstrate that layer 5a pyramidal neurons are selectively vulnerable in primary motor cortex and other cortical areas. Extensive somatic mH… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 110 publications
0
3
0
Order By: Relevance
“…2E). Subcortical projection neurons are particularly vulnerable in HD, and transduction of these cells therefore makes AAV-DB-3 a particularly attractive capsid variant for HD gene therapies 21 . As further confirmation of cortical transduction, we also observed abundant AAV-DB-3.mTFP1 signal in axons within the internal capsule (Fig 2D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2E). Subcortical projection neurons are particularly vulnerable in HD, and transduction of these cells therefore makes AAV-DB-3 a particularly attractive capsid variant for HD gene therapies 21 . As further confirmation of cortical transduction, we also observed abundant AAV-DB-3.mTFP1 signal in axons within the internal capsule (Fig 2D).…”
Section: Resultsmentioning
confidence: 99%
“…To overcome the challenges for AAV gene therapies for disorders that impact cortical and subcortical structures like HD 21, 29 , we devised an unbiased approach to identify highly potent capsids capable of transducing our target brain regions following delivery to the globus pallidus. Our libraries were based on varying AAV serotypes, required only several animals for lead selection, and the resulting capsids did not require further optimization to improve their trafficking and targeting capabilities.…”
Section: Introductionmentioning
confidence: 99%
“… 11–16 Moreover, analysis of post-mortem HD brains has shown that there is transcriptional dysregulation and somatic instability of the HTT CAG repeat in cortical neurons from HD expansion carriers. 17 However, a recent study including children and adolescents using a region of interest (ROI) approach, did not find significant differences in cortical thickness between HD expansion carriers and controls, 18 perhaps suggesting that these develop during early adulthood. 19 …”
Section: Introductionmentioning
confidence: 99%